2015
DOI: 10.2176/nmc.oa.2014-0269
|View full text |Cite
|
Sign up to set email alerts
|

Does Preoperative Measurement of Cerebral Blood Flow with Acetazolamide Challenge in Addition to Preoperative Measurement of Cerebral Blood Flow at the Resting State Increase the Predictive Accuracy of Development of Cerebral Hyperperfusion after Carotid Endarterectomy? Results from 500 Cases with Brain Perfusion Single-photon Emission Computed Tomography Study

Abstract: The purpose of the present study was to determine whether preoperative measurement of cerebral blood flow (CBF) with acetazolamide in addition to preoperative measurement of CBF at the resting state increases the predictive accuracy of development of cerebral hyperperfusion after carotid endarterectomy (CEA). CBF at the resting state and cerebrovascular reactivity (CVR) to acetazolamide were quantitatively assessed using N-isopropyl-p-[ 123 I]-iodoamphetamine (IMP)-autoradiography method with single-photon emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
53
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 36 publications
1
53
0
2
Order By: Relevance
“…1,2 Cerebral hyperperfusion syndrome after CEA is a complication of cerebral hyperperfusion; 3 its characteristic features include unilateral headache, pain in the face or eyes, seizures, and focal symptoms secondary to intracerebral hemorrhage or cerebral edema. [1][2][3][4] Intracerebral hemorrhage has a low incidence (1%), but patients with this condition have a poor prognosis.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…1,2 Cerebral hyperperfusion syndrome after CEA is a complication of cerebral hyperperfusion; 3 its characteristic features include unilateral headache, pain in the face or eyes, seizures, and focal symptoms secondary to intracerebral hemorrhage or cerebral edema. [1][2][3][4] Intracerebral hemorrhage has a low incidence (1%), but patients with this condition have a poor prognosis.…”
mentioning
confidence: 99%
“…[1][2][3][4] Intracerebral hemorrhage has a low incidence (1%), but patients with this condition have a poor prognosis. 5 Moreover, several studies have found that post-CEA hyperperfusion, even when asymptomatic, causes slight but diffuse damage to the ipsilateral cerebral cortex and white matter.…”
mentioning
confidence: 99%
See 3 more Smart Citations